2SPD-028 Referencing a midline: how to make a choice?. (24th March 2020) - Behague, P; Debailleul, M; Lampe, L; Garnier, N; Colas, V; Raoult, M; Cathelineau, F; Guenault, N; Leclercq, V; Canevet, C; Floret, E
Abstract : Background and importance: Midlines, peripheral venous catheters, allow prolonged administration of intravenous therapy to patients with low venous capital. It is essential to test them to limit further misuse or complications as part of the tendering procedure. Aim and objectives: To assess if two midlines met the expectations of medical teams and improved patient care. Material and methods: A prospective evaluation was done with Smartmidline (Vygon, G1) and ArrowMidline (Teleflex, G2) for 4 months. Midlines are given by name and placed in the operating room using a Seldinger technique. Information to nurse care services was delivered by a pharmacy intern and a public health nurse after each insertion and during changes in dressings. Medical criteria (indications, complications, catheter operating times and removal reasons) and handling criteria (evaluation sheet by installers) were listed. Results: Mean age was 74±15 years (G1) and 70±17 years (G2). There were seven successful insertions and three failures due to venous access difficulties in G1; there were eight insertions in G2. Midlines were placed by anaesthetist (94% of cases) for antibiotic therapy or nutrition. Median catheter use duration was 7 (2–24) days for G1 and 15.5 (1–65) days for G2. The reasons for withdrawal were: end of treatment (28.6% G1, 37.5% G2), accidental withdrawal by the patient (28.6% G1, 12.5% G2), thrombosis (14.3% G1), clogged catheter (12.5% G2), death (12.5% G2) and worsening of health (14.3% G1). Positive opinions were expressed regarding the length of the catheter (100% G1 vs 33% G2) and ease of installation (86% G1 vs 67% G2). Comments were made for G1 ("rigid guide") and for G2 ("complexity of handling a peel-away sheath"); 80% of installers who tested both devices preferred the Smartmidline. Conclusion and relevance: The various clinical situations and small number of patients made the medical criteria not relevant to make a choice. The handling criteria and practicality of the Smartmidline, as evaluated by caregivers, led to its recommendation. To secure its use, a hygiene protocol has been implemented in the hospital. To facilitate the interface between hospital and community carers, instructions for patients, doctors and pharmacists have to be reinforced. References and/or acknowledgements: No conflict of interest.